Search 72,388 tutors FIND TUTORS
Search for tutors
Ask a question
0 0

elimination

Tutors, please sign in to answer this question.

2 Answers

Assuming you mean...
 
4x-6y = 4   
-2x+7=-3y
 
Solving by elimination, instead of substitution...
 
Put x and y on the same side of the second equation
-2x + 3y = -7
 
Multiply the bottom equation by 2
 
                                                       4x - 6y = 4
2(-2x + 3y) = 2(-7)         =>             -4x +6y = -14
 
Add both equations together:
0 = -10
 
No solution.
 
This is why I posted the comment about you reposting the question.
 
 

Comments

If you change the -3y you posted into +3y, then of course it works out as Adam posted below.

Thus the reason I posted the comment asking you to verify that you posted the question correctly.

Have a great day.

Comment

4x - 6y =4, solve for x
 
4x = 4 + 6y
 
x = 1 + (6/4)y
 
-2x +7 = 3y 
 
-2(1 +6/4)y) + 7 = 3y     (plug in solved value for x)
 
-2 - 3y +7 = 3y
 
-6y +5 = 0 (set equal to zero and combine like terms)
 
-6y = -5
 
y = 5/6
 
use equation from above [x = 1 + (6/4)y] to find value of x
 
x = 1 + (6/4)(5/6)
 
x= 1 + 30/24
 
x = 1 + 1.25
 
x = 2.25
 
Check:
 
4x - 6y = 4
4(2.25) - 6(5/6) = 4
9 - 5 = 4
4 = 4 Check
 
-2x + 7 = 3y
-2(2.25) + 7 = 3(5/6)
 
-4.5 +7 = 2.5
2.5 = 2.5 Check

Comments

Adam,
 
When Taylor posted the question, 
 
-2x+7=   -3y
 
Not
 
-2x+7= 3y
 

Comment